Material Selection Methodology in Oil and gas Refinery using Heat Material Balances and Flow Diagram Process - Sofyan Yusuf (PSI-Aceh, 2017)
Tulisan ini memuat tentang bagaimana melakukan seleksi material pada pengilangan minyak dan gas menggunakan neraca massa dan energi dan diagram alir proses. Seleksi material adalah salah satu dari tahapan utama dalam tahap perekayasaan yang memiliki pengaruh besar terhadap biaya konstruksi pabrik. Salah satu pendekatan terbaik untuk seleksi material pada kilang pengolahan minyak dan gas bumi adalah menggunakan data neraca massa dan energi serta diagram alir proses. Neraca massa dan energi mengandung data komposisi fluida dalam satuan fraksi mol dan beberapa data operasi seperti tekanan, suhu, fasa fluida dan sebagainya yang digunakan dalam proses pemilihan material. Metode seleksi material diawali dengan perhitungan laju korosi pada masing-masing aliran pada neraca massa dan energi. Setelah data laju korosi dihitung kemudian ditentukan besarnya corrosion allowance. Jika nilai corrosion allowance diatas 6.4 mm maka dipilih material yang tahan korosi seperti stainless steel, tetapi jika nilainya dibawah 6.4 mm maka dapat dipilih material baja karbon. Setelah material yang terbaik dipilih kemudian akan dibuat diagram seleksi material dengan menggunakan data diagram alir proses. This paper give us information about how to do a material selection for oil dan gas plant using heat and material balance and flow diagram process. Material selection is one of the main phases of engineering stage that has great impact on the cost of plant construction. One of the best approaches of material selection for oil and gas plant is analyzing heat material balance and flow diagram process data. Material selection shall be reliable, cost effective and also considering market availability and constructability aspects. Heat Material Balance (HMB) contains the composition of fluids in mole fraction and others operation data such as pressure, temperature, fluid phase, etc that used in material selection process. Material selection method begins with the calculation of corrosion rate in each of the streams in HMB. After the corrosion rates are calculated then corrosion allowance (CA) will be determined. If the CA higher than 6 mm then stainless steel material will be selected, but if CA under 6 mm then carbon steel material was selected. After the best materials are selected, the Material Selection Diagram will be developed using Flow Diagram Process. Keywords: Material selection; heat material balance; flow diagram process; corrosion rate; corrosion allowance.